Journey of Exosomes in Oral Squamous Cell Carcinoma (OSCC) - Raman Dineja; R. Ashwini (Oral Oncology Reports)
“EXOSOMES” are one of the most important varieties of extracellular vesicles. They help in communication within the cell. The end version of exosomes involves in immune-modulation, stromal adaptation, and multiple biological events. Oral squamous cell carcinoma (OSCC) is considered as second most common cancer in the world. Detection of oral carcinoma happens only during the end stage which makes very poor prognosis of the condition. Now a days multiple research projects are conducted to detect and diagnose the oral squamous cell carcinoma during its early stage. In these researches exosomes play a vital role in detecting the OSCC. A PubMed search was performed for English-language, full-text available papers published from January 2005 to March 2024, focusing on exosomes role in Oral squamous cell carcinoma (OSCC). This review is done to understand the timely research where exosomes are used in various aspect in terms of OSCC. This review help to recall the yearly achievement in the diagnosis, treatment planning, prognosis of OSCC by utilising the exosomes.